Kontribusi Pencahayaan Buatan terhadap Kualitas Visual Bangunan pada Malam Hari - Mandala, Ariani; Sheila, Vania (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment), 2018)
Historical buildings frequently appear distinctive in their architectural style and ornament. These buildings have an emotional impact and forms of association to eye-witnesses. While such distinction is apparent in day-time, after dark, artificial lighting plays a critical role in conserving and transforming images. The study explores the visual qualities of historical buildings in Simpang Lima , Semarang: Lawang Sewu Building , Wisma Perdamaian , and Mandala Bhakti Museum. As landmarks of the city of Semarang, historical buildings in this area have a variety of artificial lighting systems imposed on their facade. The following paper compares building visual qualities around Simpang Lima over a 24 hour period regarding the subjective perception of the viewer. The overall impression was that significant degradation of visual quality occurred at night across all subjects. Therefore, lighting systems – lighting techniques, luminance level and choice of light colour – have played an important role in reducing the visual quality of historical buildings. Observations are made as to how this situation could be improved. Keywords: visual quality, artificial lighting, the area of Simpang Lima Semarang